Seed security factors driving farmer decisions on uptake of tissue culture banana seed in Central Uganda - Mulugo, Lucy; Kyazze, Florence Birungi; Kibwika, Paul; Oduor, Bonaventure Omondi Aman; Kikulwe, Enoch (Multidisciplinary Digital Publishing Institute, 2020)
Despite the promotion of tissue culture (TC) banana to curb the spread of diseases, farmer use of such quality planting material remains low. This study utilizes the Double-Hurdle model on cross-sectional data of 174 banana farmers in Central Uganda to analyze the drivers for uptake of TC banana plant materials. Results show acceptability (β = 0.74; p < 0.01), adaptability (β = 0.69; p < 0.01) and availability for farmer use (β = 1.04; p < 0.01) along with social influence, farmer competences and socioeconomic factors positively influence farmer uptake of the TC banana plantlets. For uptake intensity, the main drivers include acceptability (β = 0.39; p < 0.05), accessibility (β = 0.39; p < 0.01) and farmer competences. This study demonstrates that seed security factors with farmer competencies, social influence and socioeconomic factors influence farmer decisions on uptake of TC technology for banana production. Findings emphasize the need for more involvement of extension services and research institutions in the education and promotion of TC plants in farming communities. We recommend that banana TC developers and promoters focus attention on banana varieties that are acceptable and adaptable to farmer environmental conditions.